2009
DOI: 10.1038/onc.2009.151
|View full text |Cite
|
Sign up to set email alerts
|

KLF4 suppresses estrogen-dependent breast cancer growth by inhibiting the transcriptional activity of ERα

Abstract: Kruppel-like factor 4 (KLF4) is a transcription factor that participates in both tumor suppression and oncogenesis. To determine the association of KLF4 with tumorigenesis, we integrated data assembled in the Oncomine database and discovered a decrease in KLF4 gene transcripts in breast cancers. Further analysis of the database also showed a correlation between KLF4 expression and estrogen receptor-a (ERa) positivity. Knockdown of KLF4 in MCF-7 cells elevated the growth rate of these cells in the presence of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 46 publications
7
72
0
Order By: Relevance
“…KLF4 can function as either an inductive or inhibitory transcription factor acting upon, for example, various cell cycle regulatory genes or differentiation genes, including CDH1 (9,10,27,38). Loss of KLF4 in various cancers, including colon, breast, and gastric cancers, is consistent with tumor-suppressive functions (3,28,35). Ectopic overexpression of KLF4 inhibits growth and invasiveness of tumor cell lines, including prostate cancer (12,33,35,39).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…KLF4 can function as either an inductive or inhibitory transcription factor acting upon, for example, various cell cycle regulatory genes or differentiation genes, including CDH1 (9,10,27,38). Loss of KLF4 in various cancers, including colon, breast, and gastric cancers, is consistent with tumor-suppressive functions (3,28,35). Ectopic overexpression of KLF4 inhibits growth and invasiveness of tumor cell lines, including prostate cancer (12,33,35,39).…”
Section: Discussionmentioning
confidence: 97%
“…The expression of KLF4, an epithelium-determining transcription factor, decreases with progression in various epithelial cancers, including prostate cancer (3,28,33,35). Therefore, we investigated the relationship of SLUG, KLF4, and FOXA1, another epithelial transcription factor important for prostate function (15,22).…”
mentioning
confidence: 99%
“…In contrast, Akaogi et al reported that a review of nine independent, publicly available gene expression data sets revealed decreased KLF4 mRNA expression in breast cancers when compared with normal breast. In addition, KLF4 was inversely correlated with increasing tumor grade in 15 independent gene expression array analyses of breast cancer samples (17). Expression of KLF4 protein is also relatively low in breast cancer cell lines compared with non-transformed mammary epithelial cells (18).…”
Section: Krüppel-like Factor 4 (Klf4)mentioning
confidence: 95%
“…In RNAi experiments, 1 mM of siRNA solution containing a pool of two different siRNA duplexes (GenePharma Co., Ltd.) were used for each well. The sequence of siRNA duplexes was synthesized according to previous reports [11]. In the rescue experiment, NSCs were cotransfected with the Klf4 siRNA and miR-7 inhibitors at the same time.…”
Section: Transient Transfections and Cell Treatmentsmentioning
confidence: 99%